MANFAAT PENANAMAN POHON DALAM RANGKA MEMBANTU PROGRAM PENGHIJAUAN PEMERINTAH DI KELURAHAN BUGEL KECAMATAN KARAWACI KOTA TANGERANG - Dwi Respati, Rella; Isbandi, Fitri Susiswani; Cahyo Bintoro, Septian; Atikah, Atik (Gapenas Publisher, 2024)
The socialization of the benefits of tree planting in Bugel Village is part of an effort to support the greening program initiated by the Tangerang City Government. This activity was carried out by lecturers as a form of community service, with the aim of increasing awareness and participation of residents in protecting the environment through tree planting. Taking place in the NU Branch Hall of Bugel Village, this socialization was attended by residents and local community leaders. The material presented included ecological benefits, such as carbon dioxide absorption, reducing air pollution, and preventing soil erosion, as well as benefits for health and quality of life, including reducing stress and improving air quality. In addition, the economic and social benefits of greening were also discussed, such as increasing property values ??and creating green spaces that support social interaction. This activity aims to build collective awareness of residents in preserving the environment, as well as contributing to the achievement of greening targets in urban areas. Through this socialization, it is hoped that residents can be more actively involved in the tree planting movement and support the creation of a greener and more sustainable environment in Tangerang City.